Investigating high-energy Hermite–Gaussian and vortex laser generation in alexandrite - Enlin Cai; Shuaiyi Zhang; Tao Li; Jie Wang; Min Chen (High Power Laser Science and Engineering, 2025)
This paper presents an investigation of the secondary saturation characteristics of a HfTe2 saturable absorber. Pulse energies of 5.85 and 7.4 mJ were demonstrated with a high-order Hermite–Gaussian (HG) laser and a vortex laser, respectively, using alexandrite as the gain medium. To the best of our knowledge, these are the highest pulse energies directly generated with HG and vortex lasers. To broaden the applications of high-energy pulsed HG and vortex lasers, wavelength tuning in the region of 40 nm was achieved using an etalon.